2020
DOI: 10.1186/s13690-020-0398-1
|View full text |Cite
|
Sign up to set email alerts
|

Field-testing of a rapid survey method to assess the prevalence and causes of hearing loss in Gao’an, Jiangxi province, China

Abstract: Background: The Rapid Assessment of Hearing Loss (RAHL) survey protocol aims to measure the prevalence and causes of hearing loss in a low cost and rapid manner, to inform planning of ear and hearing services. This paper reports on the first field-test of the RAHL in Gao'an County, Jiangxi Province, China. This study aimed to 1) To report on the feasibility of RAHL; 2) report on the estimated prevalence and causes of hearing loss in Gao'an. Methods: A cross-sectional population-based survey was conducted in Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(52 reference statements)
0
3
2
Order By: Relevance
“…Our estimate of unmet need for near vision glasses (44.9%) was similar when compared to this same Tanzanian study's population aged 35+ years which found an uncorrected presbyopia prevalence of 46.5% [22] and slightly lower than studies in similar age groups in Ghana (64%) [23] and Nepal (66.1%) [24]. For hearing, the need for hearing aids (25.5%) in this study is lower than estimates from RAHL surveys, which used the same ear/hearing assessment methods, in Malawi (30.8%) [25] and China (54%) [26], likely because the focus was people 35+ compared to 50+ in the other surveys. The low coverage (<1%) is similar across all three studies [25,26].…”
Section: Estimated Population Ad Need and Coveragecontrasting
confidence: 78%
See 1 more Smart Citation
“…Our estimate of unmet need for near vision glasses (44.9%) was similar when compared to this same Tanzanian study's population aged 35+ years which found an uncorrected presbyopia prevalence of 46.5% [22] and slightly lower than studies in similar age groups in Ghana (64%) [23] and Nepal (66.1%) [24]. For hearing, the need for hearing aids (25.5%) in this study is lower than estimates from RAHL surveys, which used the same ear/hearing assessment methods, in Malawi (30.8%) [25] and China (54%) [26], likely because the focus was people 35+ compared to 50+ in the other surveys. The low coverage (<1%) is similar across all three studies [25,26].…”
Section: Estimated Population Ad Need and Coveragecontrasting
confidence: 78%
“…For hearing, the need for hearing aids (25.5%) in this study is lower than estimates from RAHL surveys, which used the same ear/hearing assessment methods, in Malawi (30.8%) [25] and China (54%) [26], likely because the focus was people 35+ compared to 50+ in the other surveys. The low coverage (<1%) is similar across all three studies [25,26].…”
Section: Estimated Population Ad Need and Coveragecontrasting
confidence: 64%
“…The observed incidence of HL in our study was lower than total prevalence reported by another study in China (1). However, results of this study were closer to prevalence of disabling HL ranged from 8.0 to 16.1% in several surveys (64)(65)(66)(67). Therefore, we applied the definition in the present study to minimize potential measurement error and focus on poor HL.…”
Section: Discussionmentioning
confidence: 52%
“…When adjusting the grades of hearing impairment according to WHO recommendations, the prevalence of moderate to severe hearing loss among the Bangkok population was 2.8%, consistent with the nding of Ferrite's study (2017) (13) where the prevalence of moderate or greater hearing loss in northwest Cameroon was 3.6%. However, the prevalence was lower compared to studies in the Philippines and in China with the prevalence of 15 and 16.3%, respectively (9,14). The differences in the prevalence of hearing loss/hearing impairment were probably due to factors such as population sizes, sampling strategies, de nitions or criteria for grading hearing loss, and the prevalence of the outer and middle ear diseases in the population.…”
Section: Discussionmentioning
confidence: 65%

Hearing Health Survey of Population in Bangkok

Ruencharoen,
Lertsukprasert,
Suvanich
et al. 2023
Preprint